2021
DOI: 10.1080/01652176.2021.1992803
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of notched and fragmented QRS complex in dogs with naturally occurring myxomatous mitral valve disease

Abstract: Background: Myxomatous mitral valve disease (MMVD) is the most common cardiac disease in dogs. The association of QRS notching (nQRS) or fragmentation (fQRS) with disease severity is currently unknown.Objective: To assess the prevalence of nQRS and fQRS in dogs with MMVD and its severity according to ACVIM classification and to compare the results with a group of healthy dogs. Methods:This retrospective cross-sectional study included 34 healthy control dogs and 155 dogs with spontaneous MMVD (42% of dogs in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…But while multiple studies have demonstrated that S-T segment elevation can be a sign of myocardial ischemia, S-T segment elevation as an indicator of cardiac damage specifically from PMC is an occasional but inconsistent finding (18). Conduction abnormalities, as seen with notched QRS complexes have been reported in a variety of cardiac diseases in human and canines, but again are occasionally but not consistently seen in puppies who later succumb to PMC (18, [28][29][30].…”
Section: Electrocardiographymentioning
confidence: 99%
“…But while multiple studies have demonstrated that S-T segment elevation can be a sign of myocardial ischemia, S-T segment elevation as an indicator of cardiac damage specifically from PMC is an occasional but inconsistent finding (18). Conduction abnormalities, as seen with notched QRS complexes have been reported in a variety of cardiac diseases in human and canines, but again are occasionally but not consistently seen in puppies who later succumb to PMC (18, [28][29][30].…”
Section: Electrocardiographymentioning
confidence: 99%